Reporting in the midst of helplessness: Analysis of the Mexican journalists’ protection measures from the local context - De León Vázquez, Salvador (2020)
The aim of this paper is to present a formal analysis of the local laws related to Mexican journalists’ protection, and compare it with news workers’ perceptions on this issue. The starting point is a theoretical discussion on the current risk of practicing journalism, and the need to provide local legal assistance. This is followed by an argumentative formal analysis of the local laws, complemented by a set of 55 semi-structured interviews with journalists from the same places, which were conducted between February 2017 and August 2018. The findings show three kinds of legal protection: social, civil, and physical. On the contrary, based upon their own experiences, reporters do not trust in those laws. The final argument is that the local context matters in order to understand how the protection measures operate in the most dangerous country in the world for journalism.